2018
DOI: 10.7759/cureus.2650
|View full text |Cite
|
Sign up to set email alerts
|

A Benign Rare Lesion of the Breast: Giant Epidermal Inclusion Cyst

Abstract: An epidermal inclusion cyst can be seen at any location. Epidermal cysts are commonly found on the scalp, face, trunk, neck, and extremities. They are rarely seen in the breast parenchyma. These benign lesions are important in that they may undergo neoplastic differentiation, although very rarely. Epidermoid cysts usually develop as a result of the implantation of superficial epidermal tissue into the dermis or subcutaneous tissue after trauma or surgical procedures. In this study, a 37-year-old female patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…In addition to the conventional mammographic features, CESM revealed more details of the lesion. Subtracted images showed that the cyst had peripheral rim enhancement, which has been previously shown on MRI, 2 , 10 , 20 and part of the cyst wall was thickened, which was consistent with the CT findings. The intensity in the cyst was low compared with the background enhancement, revealing the cystic nature of the lesion.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to the conventional mammographic features, CESM revealed more details of the lesion. Subtracted images showed that the cyst had peripheral rim enhancement, which has been previously shown on MRI, 2 , 10 , 20 and part of the cyst wall was thickened, which was consistent with the CT findings. The intensity in the cyst was low compared with the background enhancement, revealing the cystic nature of the lesion.…”
Section: Discussionsupporting
confidence: 89%
“…Paliotta et al identified a total of 91 patients affected by epidermal inclusion cysts of the breast through a search of the literature in 2014 [2], and thereafter, sporadic case reports of epidermal inclusion cysts have been published until recently [7,915]. Epidermal inclusion cysts of the breast typically develop during the fifth decade of life [2], and are usually located in the skin; however, they can develop in unusual locations, such as cutaneously on the nipple or areola or intra-parenchymally in the subor peri-areolar regions.…”
Section: Discussionmentioning
confidence: 99%
“…Mammographic presentation of epithelial inclusion cysts of the breast usually includes a circumscribed iso- or hyperdense mass [2,21] and can sometimes be accompanied by microcalcifications [21]. Magnetic resonance imaging features were reported in a few cases, which were circumscribed masses with a fluid-like signal of a variable low-signal component on T2-weighted images and peripheral rim enhancement [2,5,6,9] or no enhancement [22] on contrast-enhanced images.…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal inclusion cysts are commonly found on the scalp, face, neck, trunk, and extremities and typically present with classic dermal findings of an erythematous papule with a central punctum [1][2][3][4]. Based on a literature review from 2015 by Paliotta et al, 82 cases of epidermal inclusion cyst in the breast were reviewed and a total of 90 cases have been reported in the international literature.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a literature review from 2015 by Paliotta et al, 82 cases of epidermal inclusion cyst in the breast were reviewed and a total of 90 cases have been reported in the international literature. Causes of epidermal inclusions cysts include congenital factors, obstruction of a hair follicle, epidermal fragment implantation into the dermis secondary to damage to the epidermis, or in the case of fibrocystic disease development of squamous metaplasia of columnar cells within a dilated duct [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%